Cell-mimicking polyethylene glycol-diacrylate based nanolipogel for encapsulation and delivery of hydrophilic biomolecule - Liew, Wen Jie Melvin; Wong, Yee Shan; Parikh, Atul N.; Venkatraman, Subbu S.; Cao, Ye; Czarny, Bertrand (Frontiers in Bioengineering and Biotechnology, 2023)
Lipid based nanoparticulate formulations have been widely used for the encapsulation and sustain release of hydrophilic drugs, but they still face challenges such as high initial burst release. Nanolipogel (NLG) emerges as a potential system to encapsulate and deliver hydrophilic drug while suppressing its initial burst release. However, there is a lack of characterization of the drug release mechanism from NLGs. In this work, we present a study on the release mechanism of hydrophilic Dextran-Fluorescein Isothiocyanate (DFITC) from Poly (ethylene glycol) Diacrylate (PEGDA) NLGs by using different molecular weights of PEGDA to vary the mesh size of the nanogel core, drawing inspiration from the macromolecular crowding effect in cells, which can be viewed as a mesh network of undefined sizes. The effect is further characterized and validated by studying the diffusion of DFITC within the nanogel core using Fluorescence Recovery after Photobleaching (FRAP). Our work showed that the mesh size of the NLGs can be controlled by using different Mw of PEGDA and the release of hydrophilic DFITC can be sustained while suppressing the initial burst release, up to 10-fold more for crosslinked PEGDA 575 NLGs. This is further validated by FRAP which showed that the diffusion of DFITC is hindered by the decreasing mesh sizes in the NLGs, as a result of lower mobile fractions. These findings will be useful for guiding the design of NLGs for other different types of nanogel cores and other nanogel core-based nanoparticles for encapsulation and release of hydrophilic biomolecules.